Innovation and strategy - Varadarajan, Rajan; Jayachandran, Satish (Review of marketing research ;, 2018)
Innovation is the process of value creation through use of relevant knowledge, capabilities and resources for conversion of ideas into new products, processes and practices, and improvements in existing products, processes and practices. Innovations of various types and forms are crucial to achieving and sustaining a competitive advantage in the marketplace, the principal focus of competitive strategy. Product innovations play a central role in various strategic marketing contexts such as meeting consumers' needs and wants, responding to changes in consumers' preferences, shaping consumers' preferences, entering new markets, enhancing a firm's market position in presently served product-markets, differentiating the firm's product offerings from competitors' offerings, neutralizing the effects of competitors' actions, and preemption and deterrence of competitors. Against this backdrop, articles published in this volume focus on substantive issues in innovation, marketing strategy, and the nexus of innovation and marketing strategy. The substantive issues addressed in these articles include sources of innovation, customer involvement in innovation, innovations in a digital environment, innovations in an information rich environment, the role of market foresight and design orientation as organizational capabilities in new product development and new product performance, and the effects of market orientation, organizational culture, trust and commitment on business performance.